On the possibility of the existence of the spatially periodical Bose condensate - Peletminsky, A.S.; Peletminsky, S.V.; Slyusarenko, Yu.V. (Condensed Matter Physics, 2000)
The possibility of constructing the theory relating to a spatially periodical Bose condensate in the model of a weakly nonideal Bose gas is studied. Equations for determining a spatially periodical order parameter at the temperature T = 0 are formulated and their one-periodical solutions are obtained based on the isolated Bose condensate method. Here it is possible to neglect the contribution of quasiparticles to the thermodynamics of a boson system. The problems of thermodynamic stability of the spatially periodical Bose condensate are presented in short.